2008
DOI: 10.1007/s10067-008-0970-5
|View full text |Cite
|
Sign up to set email alerts
|

Case reports: testicular pain as a manifestation of polyarteritis nodosa

Abstract: Polyarteritis nodosa (PAN) is a necrotising vasculitis of medium-sized vessels of unknown origin. This type of vasculitis is usually systemic, but restriction to a single organ, for example the testis, the appendix or the gall bladder, can occur. Testicular pain or tenderness are frequent clinical features. In this report, we present three cases of PAN. In every patient, testicular pain was the main symptom or first sign of systemic disease. We state that a thorough history taking, clinical examination and bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…With evidence of neurological involvement, our patient was started on high-dose intravenous methylprednisone and cyclophosphamide with good effect. In this case, we also report successful conservative management with normal endocrine testicular function (Table 2) [6-9]. The facial weakness resolved after 3 months.…”
Section: Discussionmentioning
confidence: 73%
“…With evidence of neurological involvement, our patient was started on high-dose intravenous methylprednisone and cyclophosphamide with good effect. In this case, we also report successful conservative management with normal endocrine testicular function (Table 2) [6-9]. The facial weakness resolved after 3 months.…”
Section: Discussionmentioning
confidence: 73%
“…PAN commonly affects the kidneys, gastrointestinal tract, skin, nerves, joints, and muscles. PAN can also present as an isolated self-limited disorder, as in our case (9). It is a rare disease; in European countries the incidence ranges from 0 to 1.6 cases per million, and the prevalence is approximately 31 cases per million (10,11).…”
Section: Discussionmentioning
confidence: 77%
“…There have been several published case reports where testicular pain was the principal symptom/sign of PAN 3 4. The pathogenesis of the testicular pain is thought to be due to testicular artery vasculitis and this theory has been supported by ultrasonography of the testicles of patients with clinical evidence of PAN: Kolar et al demonstrated vasculitis of the testicular artery in a patient who was diagnosed with PAN 5.…”
Section: Discussionmentioning
confidence: 98%